Intra-and interpersonal determinants of sugar sweetened beverage and daily sugar intake among adolescent girls in Tasikmalaya City: A cross-sectional study - Prima Endang Susilowati; Rizka Fikrinnisa; Nisatami Husnul; Lilik Hidayanti (AcTion: Aceh Nutrition Journal, 2026)
Sugar Sweetened Beverages (SSBs) are a type of high-energy drink favored by adolescents. Determinants within the individual and interactions with others can influence SSB intake. This study aimed to understand the association between intra- and interpersonal determinants of the frequency of SSBs consumption and daily sugar intake in adolescent girls. This study used a cross-sectional design, with 342 subjects selected from1425 junior high school students in Tasikmalaya City. Data collection on daily sugar intake used the SQ-FFQ, while the frequency of SSBs consumption was assessed using a questionnaire. Data analysis was performed using chi-square and logistic regression. The results showed that most participants frequently consumed SSBs (83%) and had excessive daily sugar intake (61.1%). Sweet taste preference (p=0.041; aOR 1.919[1.028–3.585]), advertising influence (p=0.013; aOR 2.141 [1.176–3.898]), and access to SSBs at school (p=0.033; aOR 2.594 [1.082–6.214]) were associated with the frequency of consumption. The frequency of SSBs consumption (p=0.000; aOR 7.293 [3.681–14.452]) and maternal education (p=0.044; aOR 1,662 [1.013 – 2.726]) were associated with daily sugar intake. Access to SSBs at school was the most dominant determinant associated with the frequency of SSBs consumption. School-based interventions can include providing drinking water, especially during lunchtime.